The impact of weight gain–loss cycles on neuromuscular efficiency and skill performance in individual and team sports: Body weight management in amateur athletes - BOUAITA, Toufik; BOUHALI, Oussama; BELILI, Amar; BOUADJILA, Omar; GHELLAB, Hakim; KHALFA, Imededdin (The International tax journal, 2026)
This quasi-experimental study examined the impact of repeated weight gain–loss cycles on selected indicators of neuromuscular efficiency (explosive strength, reaction time) and skill performance in amateur athletes from individual and team sports, considering somatotype as a moderating factor of response variability. The sample comprised 40 amateur athletes regularly engaging in weight cycling, assessed at three time points (pre-cycle T1, mid-cycle T2, post-cycle T3) for body composition, vertical jump performance, reaction time, and sport-specific skills. The findings revealed significant declines in vertical jump height, reaction time, and skill performance at T2 compared with T1, followed by partial recovery at T3 without full restoration to baseline, alongside a greater decrement in skill performance in individual-sport athletes and a clear association between the magnitude of weight loss and the severity of functional impairments. The discussion further suggested that mesomorphic athletes appear more resilient to weight fluctuations than endomorphic counterparts, underscoring the importance of individualized weight-cycle planning based on somatotype and sport-specific demands.